The design and psychometric evaluation of a COVID-19 social stigma questionnaire in nurses - Narges Rahmani; FatemehSadat SeyedNematollah Roshan; Majedeh Nabavian; Hossein Alipour (BMC, 2023)
Abstract Background The patient's fear of social reactions, the disease stigma, and being a transmission agent is a psychological and social consequence of contracting some diseases, especially infectious ones, in any society. The present study aimed to design and psychometrically evaluate a COVID-19 social stigma questionnaire in nurses. Methods This mixed-method study was conducted using a sequential exploratory approach according to the Creswell method in Mazandaran Province (Iran) during 2021-22. The study was performed in three phases: (1) a qualitative phase to explain the key concept, (2) designing the scale items, and (3) an experimental phase with the scale psychometric evaluation. In the first phase, nurses' experiences regarding the concept of COVID-19 social stigma were evaluated using a qualitative method with an inductive qualitative content analysis approach. In this phase, the lived experiences of 12 nurses working at hospitals of Babol University of Medical Sciences were extracted through in-depth interviews with semi-structured questions and analyzed by conventional content analysis. The main classes are contradictory feelings, rejection, and adaptation strategies. In the second phase, the designed items were validated by determining face validity, content validity, and construct validity using exploratory factor analysis (EFA). In addition, the scale's reliability was determined through internal consistency and stability. Results Following the study's first phase, a pool of questions with 64 initial items was formed. After evaluating face and content validity, the number of items was reduced to 24 cases. An excellent total content validity (S-CVI/Ave) of 0.93 was calculated for the scale. According to EFA outputs, three factors accounted for the most variance (52.82%), and four items were excluded in this phase. The Kaiser-Meyer-Olkin (KMO) statistic and Bartlett's test of sphericity were calculated at 0.776 and P < 0.001, respectively. The results of Cronbach's alpha (0.796) and intraclass correlation (0.793) indicated the correlation and internal consistency of the scale. Conclusion This scale can help healthcare managers and policymakers apply necessary protective measures by evaluating the social stigma of COVID-19 in nurses and emerging infectious diseases that may occur in the future.